1992
DOI: 10.1002/hon.2900100209
|View full text |Cite
|
Sign up to set email alerts
|

The biological and clinical significance of the KI‐67 growth fraction in multiple myeloma

Abstract: We tested the significance of the Ki-67 plasma cell growth fraction in 49 bone marrow samples from 42 patients with multiple myeloma (MM). As a new approach to study myeloma cell proliferation, strong positivity of the CD38 antigen as plasma cell related feature was simultaneously evaluated with nuclear Ki-67 expression in a flow cytometric double immunofluorescence assay. Mean Ki-67 values were significantly higher in MM at relapse (22.4 per cent +/- 10.4) as compared with MM at diagnosis (11.9 per cent +/- 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 30 publications
(2 reference statements)
2
16
0
3
Order By: Relevance
“…To study cell-cycle progression, we used a flow cytometric assay using Ki67 and PI and observed that the baseline S ϩ G 2 M fraction correlates with disease progression, confirming previous reports. 25,26 As far as we know, ours is the first demonstration of G 1 /S progression in a series of primary MM cells in response to mitogenic stimuli. We validated our results using BrdU and 3 H-thymidine incorporation, standard assays for DNA synthesis.…”
Section: Discussionmentioning
confidence: 69%
“…To study cell-cycle progression, we used a flow cytometric assay using Ki67 and PI and observed that the baseline S ϩ G 2 M fraction correlates with disease progression, confirming previous reports. 25,26 As far as we know, ours is the first demonstration of G 1 /S progression in a series of primary MM cells in response to mitogenic stimuli. We validated our results using BrdU and 3 H-thymidine incorporation, standard assays for DNA synthesis.…”
Section: Discussionmentioning
confidence: 69%
“…Unlike well-differentiated plasma cell neoplasms, plasmablastic plasma cell myelomas usually have an extremely high proliferation index and alterations in cell cycle regulators such as p16, p21, and p53. 10,[36][37][38] In situ hybridization assays for EBER were positive in all five cases of plasmablastic lymphoma analyzed, and were negative in all plasmablastic plasma cell myelomas. Although the number of cases analyzed is relatively small, the difference in EBER expression between plasmablastic lymphoma and plasma cell myeloma was highly statistically significant (Po0.002).…”
Section: Discussionmentioning
confidence: 99%
“…In order to have comparable results we used the propidium iodide stain, which easily detects the S-phase. The Ki-67 index evaluates all the cell cycle phases [46,47] and represents rather the "cycling" potential, and it does not necessarily correspond to proliferation detected by the BrdUrd or PC-PI techniques. Other methods such as immunohistochemical analysis of proliferating cell nuclear antigen (PCNA) [48], detection of AgNORs (argyrophillic proteins associated with the nucleolar organizer regions) in histological samples [49], cyclin D1 detection [50] and some others are not widely used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%